Immune-Mediated Necrotizing Myopathy Initially Presenting as Erythema Nodosum - Ying S; Li S; Tang S; Sun Q; Fang D; Li Y; Zhu D; Fang H; Qiao J (Dove Medical Press, 2020)
Shuni Ying, Sheng Li, Shunli Tang, Qingmiao Sun, Deren Fang, Yali Li, Dingxian Zhu, Hong Fang, Jianjun Qiao Department of Dermatology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310003, People’s Republic of ChinaCorrespondence: Jianjun Qiao; Hong FangDepartment of Dermatology, The First Affiliated Hospital, Zhejiang University School of Medicine, No. 79, Qingchun Road, Hangzhou 310003, People’s Republic of ChinaTel +86-571-87236385Email qiaojianjun@zju.edu.cn; fanghongzy@zju.edu.cnAbstract: Immune-mediated necrotizing myopathy (IMNM) is a type of autoimmune myopathy characterized by severe diffuse proximal myofiber necrosis in the context of inflammatory myopathy. Autoantibodies of anti-signal recognition particle and anti-hydroxy-3-methylglutaryl-CoA reductase are two antibodies specific to IMNM. Erythema nodosum (EN) is often accompanied by various systemic diseases, such as autoimmune diseases. Herein, we report a female patient with signal recognition particle-associated IMNM, with EN as the first presentation. She showed significant clinical improvement after the initiation of glucocorticoids, intravenous immunoglobulin, rituximab, and mycophenolate mofetil. This case indicates that IMNM can initially present as EN. IMNM and EN might have overlapping pathogeneses.Keywords: immune-mediated necrotizing myopathy, erythema nodosum, autoantibody